An ethics for today: finding common ground between philosophy and religion - Rorty, Richard (Columbia University Press, 2011)
Richard Rorty is famous, maybe even infamous, for his philosophical nonchalance. His groundbreaking work not only rejects all theories of truth but also dismisses modern epistemology and its preoccupation with knowledge and representation. At the same time, the celebrated pragmatist believed there could be no universally valid answers to moral questions, leading to a complex view of religion rarely expressed in his writings. In this posthumous publication, Rorty, a strict secularist, finds in the pragmatic thought of John Dewey, John Stuart Mill, Henry James, and George Santayana